Dialogues on using the veil (hijab): empowerment, identity and religiosity - Ferreira, Francirosy Campos Barbosa (Universidade Estadual Paulista / UNESP, 2014)
The aim of this paper is to propose a discussion on the use of Islamic headscarves (hijab, etc). The use of Islamic dress should be analyzed from the perspective of empowerment, identity and religiosity of Muslim women. This does not imply the separation of these concepts, but rather a consolidation of perspectives that sometimes blend or separate, depending on the subject and interlocutors in question.